2021
DOI: 10.1002/clc.23726
|View full text |Cite
|
Sign up to set email alerts
|

Association of coronary microvascular dysfunction and cardiac bridge integrator 1, a cardiomyocyte dysfunction biomarker

Abstract: Background: Coronary microvascular dysfunction (CMD) is associated with heart failure with preserved ejection fraction (HFpEF); however, pathophysiology is not well described. Hypothesis:We hypothesized that CMD in women with suspected ischemia with no obstructive coronary artery disease (INOCA) is associated with cardiomyocyte dysfunction reflected by plasma levels of a cardiomyocyte calcium handling protein, cardiac bridge integrator 1 (cBIN1). Methods: Women with suspected INOCA undergoing coronary function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Single studies have reported higher levels of serotonin, 75 stearic acid, 76 ornithine, 76 cardiac bridge integrator 1, 77 galactin‐3, 14 galectin‐4, 34 angiopoietin‐2 and tyrosine kinase‐2 receptor, 78 lymphocyte DNA damage, 79 NT‐proBNP (N‐terminal pro‐B‐type natriuretic peptide), 62 and red blood cell distribution width 62 in CMD compared with control subjects, and no difference in apolipoprotein‐C levels in CMD compared with controls. 31 In a study of 97 subjects with CMD, galectin‐4 levels correlated with myocardial blood flow reserve.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Single studies have reported higher levels of serotonin, 75 stearic acid, 76 ornithine, 76 cardiac bridge integrator 1, 77 galactin‐3, 14 galectin‐4, 34 angiopoietin‐2 and tyrosine kinase‐2 receptor, 78 lymphocyte DNA damage, 79 NT‐proBNP (N‐terminal pro‐B‐type natriuretic peptide), 62 and red blood cell distribution width 62 in CMD compared with control subjects, and no difference in apolipoprotein‐C levels in CMD compared with controls. 31 In a study of 97 subjects with CMD, galectin‐4 levels correlated with myocardial blood flow reserve.…”
Section: Resultsmentioning
confidence: 99%
“… 31 In a study of 97 subjects with CMD, galectin‐4 levels correlated with myocardial blood flow reserve. 34 The studies measuring serotonin, 75 cardiac bridge integrator 1, 77 galectin‐4, 34 and apolipoprotein‐C 31 assessed CMD directly by invasive and noninvasive techniques. The Klotho gene encodes a transmembrane protein, and the extracellular part of it is cleaved and can be measured in the blood.…”
Section: Resultsmentioning
confidence: 99%
“…rs6733839 is located near the bridging integrator 1 (BIN1) gene, which in turn affects the accumulation of the two major pathological hallmarks of AD, namely β-amyloid and Tau ( 57 ). BIN1 has also been found to be a regulator of transverse tubule function and calcium signaling in cardiomyocytes, and is associated with abnormal cardiac contraction, increasing the likelihood of malignant arrhythmias before heart failure ( 58 ); plasma levels of cardiac bridging integrator 1 (cBIN1) also indicative of the effects of coronary microvascular dysfunction on cardiomyocytes ( 59 ). Thus, this may be a potential mechanism for the relationship between the two diseases.…”
Section: Discussionmentioning
confidence: 99%
“…A novel plasma biomarker of cardiomyocyte calcium handling protein, cardiac bridge interrogator 1 (cBIN-1), was recently found to be elevated in women with INOCA, reflecting cardiomyocyte tubule dysfunction [ 87 ]. Furthermore, higher cBIN1 score was associated with coronary endothelial dysfunction in these women.…”
Section: Pre-hfpef Characteristics In Women With Inocamentioning
confidence: 99%